TOXOPLASMOSIS DALAM KEHAMILAN - Sri Wahyuni (Balai Penelitian dan Pengembangan Kesehatan Banjarnegara Badan Litbangkes Kemenkes RI, 2013)
ABSTRACT. Toxoplasmosis is one zoonosis caused by toxoplasmosis gondii that can infected pets and human.Infection in woman pregnant, frequently asymptomatic. While impact at this disease woman pregnant for herpregnancy, specially at third trimester pregnant were hidrocephalus, chorioretinitis, deaf or epilepsi.Toxoplasmosis is a disease caused by toxoplasma gondii, transmitted to human by eating food under cooked,infected meat or handling soil or cat feces that contain the parasite. The route of infection in to human by aquiredor congenital variation impact of congenital toxoplasmosis were chorioretinitis, hydrocephalus, intracranialcalcificatio. Laboratorys tests are very important of clinical sign is asymtomatic. Test that commonly usedmoreanti toxoplasma Ig G, Ig M, Ig A and Aviditas Anti Toxoplasma. Primmary and secondary prevention is important.Treatment to toxoplasmosis with spiramycine is effective. Toxoplasmosis infection prevention could be done byavoid risk factor of toxoplasmosis ie not eating raw specially undercooked meat, not contact with animal'sinfected. Toxoplasmosis treatment in pregnancy is needed include abortion and antibiotic support to infant couldbe done according to discussion from doctor, patients and her husband.